2016
DOI: 10.1002/mbo3.391
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa in premise plumbing of large buildings

Abstract: Pseudomonas aeruginosa is an opportunistic bacterial pathogen that is widely occurring in the environment and is recognized for its capacity to form or join biofilms. The present review consolidates current knowledge on P. aeruginosa ecology and its implication in healthcare facilities premise plumbing. The adaptability of P. aeruginosa and its capacity to integrate the biofilm from the faucet and the drain highlight the role premise plumbing devices can play in promoting growth and persistence. A meta‐analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
109
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(120 citation statements)
references
References 168 publications
(271 reference statements)
8
109
1
2
Order By: Relevance
“…Opportunistic bacteria, such as Pseudomonas aeruginosa [13], might better serve to indicate the occurrence of some of the nonfaecal pathogens [12], especially in bathing waters [14]. Taking into account the results found in a study from Mariño and coworkers, where a positive correlation was found between skin infections and the presence of P. aeruginosa in seawater [14], this opportunistic bacteria [13] might better serve to indicate the occurrence of some nonfaecal pathogens in bathing waters [12].Being rod-shaped, gram-negative, facultative aerobic bacterium, P. aeruginosa has minimal survival requirements [15,16] and a remarkable adaptation ability towards a variety of environmental conditions, being able to thrive in soil, water, animal hosts, hospital settings, soap, and even distilled water [17][18][19][20]. P. aeruginosa, as the origin of an extensive variety of infections, is a main cause of illness in immunocompromised individuals [21].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Opportunistic bacteria, such as Pseudomonas aeruginosa [13], might better serve to indicate the occurrence of some of the nonfaecal pathogens [12], especially in bathing waters [14]. Taking into account the results found in a study from Mariño and coworkers, where a positive correlation was found between skin infections and the presence of P. aeruginosa in seawater [14], this opportunistic bacteria [13] might better serve to indicate the occurrence of some nonfaecal pathogens in bathing waters [12].Being rod-shaped, gram-negative, facultative aerobic bacterium, P. aeruginosa has minimal survival requirements [15,16] and a remarkable adaptation ability towards a variety of environmental conditions, being able to thrive in soil, water, animal hosts, hospital settings, soap, and even distilled water [17][18][19][20]. P. aeruginosa, as the origin of an extensive variety of infections, is a main cause of illness in immunocompromised individuals [21].…”
mentioning
confidence: 99%
“…Being rod-shaped, gram-negative, facultative aerobic bacterium, P. aeruginosa has minimal survival requirements [15,16] and a remarkable adaptation ability towards a variety of environmental conditions, being able to thrive in soil, water, animal hosts, hospital settings, soap, and even distilled water [17][18][19][20]. P. aeruginosa, as the origin of an extensive variety of infections, is a main cause of illness in immunocompromised individuals [21].…”
mentioning
confidence: 99%
“…This pathogen may be problematic due to its ability to form biofilms-multicellular aggregates embedded in selfproduced polymeric substances-that shield bacterial cells from antibacterial agents (such as disinfectants in water premise plumbing [1], host immune defenses [2,3]). It is well documented that biofilms greatly contribute to the establishment of chronic infections, including chronic pneumonia in cystic fibrosis patients, relapsing and chronic wound and ear infections, as well as medical device-related infections (3).…”
mentioning
confidence: 99%
“…Over the last decade, the interest in premise plumbing from the water industry has increased. Numerous studies have investigated different issues surrounding premise plumbing, such as corrosion [78][79][80][81] and the growth of opportunistic pathogens [82][83][84][85][86][87][88]. Premise plumbing systems are an area of the distribution system that can be overlooked by water utilities, since most premise plumbing systems are not owned or maintained by the utility and most drinking water regulations do not address premise plumbing, with the exception of the Lead and Copper Rule (LCR).…”
Section: Nitrification In Premise Plumbingmentioning
confidence: 99%